Spanish seamen (circular) - Tewson, Vincent
025-0033-001 Telegraphic Address: TRADUNIC, SOWEST, LONDON. Telephone: Victoria 9020. Trades Union Congress GENERAL SECRETARY SIR WALTER CITRINE KBE To whom all communications should be addressed. Department International Our ref. HVT/AC/321. Your ref. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1. 31st July, 1939. SPANISH SEAMEN. We have been informed by the Basque Delegation that the Basque Nationalist Parties have made arrangements with the Venezuelan Government for the emigration to Venezuela of a number of the seamen in this country who are members of the Basque Nationalist Parties. You may be approached by one or more of these men to solicit your assistance in the securing of two papers which the Venezuelan Government demands. The first is a certificate of general health, which will also indicate that the man has been vaccinated against smallpox and typhoid (as is true in all cases) and the second a certificate to the effect that the man has been of good behaviour, which should be applied for to the local police. I know you will be glad to do what you can to assist in this matter. This project is, by the way, quite apart from the general scheme of emigration, which we are still pursuing. Yours sincerely, H. V. TEWSON. Assistant Secretary. 292/946/25b/29